(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1990)
Excavation by the author, K Antonio and R Gourlay in Dornoch Forestry Commission tree nursery, in January 1980, revealed a cist with massive capstone, an all-over-corded beaker, five arrowheads, a bracer, a strike-a-light and iron ore nodule, a fragment of Grooved ware and remains of an inhumation and a cremation. The contents of the cist were heavily disturbed by animal burrows. No radiocarbon date was obtained because of the high likelihood that there would be insufficient carbon in the bones for assay.